3 The detection of cardiac amyloidosis using extracellular volume quantification by computed tomography. (May 2018) - Scully, Paul R; Treibel, Thomas A; Klotz, Ernst; Castle, Emily; Yap-Sanderson, Joanna; Saberwal, Bunny; Ahmadvazir, Shahram; Gangil, Nishant; Davies, Ceri; Mullen, Michael; Kennon, Simon; Ozkor, Muhiddin; et al.
Abstract : Background: Amyloidosis is characterised by the extracellular deposition of misfolded protein, markedly increasing the myocardial extracellular volume (ECV). Cardiac transthyretin amyloidosis co-exists in up to 1 in 7 elderly patients with severe aortic stenosis (AS) referred for transcatheter aortic valve implantation (TAVI). 99m Tc-3, 3-diphosphono-1, 2-propanodicarboxylic acid (DPD) scintigraphy can detect this, but screening patients using ECV quantification by computed tomography (ECVCT ) in the same sitting as their TAVI work-up CT is an attractive concept, which we sought to investigate. Methods: Elderly patients (aged ≥75) with severe AS referred for TAVI were recruited as part of the ATTRact-AS study (NCT03029026 ). DPD scans were graded using the Perugini scoring system. Additional pre- and 3 min post contrast 'axial shuttle mode' datasets were acquired for ECVCT . These datasets were averaged, registered with the CT angiogram and subtracted. Inputting the haematocrit enabled estimation of the myocardial ECV. Results: 30 patients underwent ECVCT (aged 87±6 years, 43% male), including 10 with evidence of cardiac amyloid on DPD scintigraphy (4 Perugini grade 1, 6 grade 2). Total myocardial ECVCT was 29%±3% for grade 0, 31±4% for grade 1 and 41%±9% for grade 2 (p<0.001 by ANOVA). ROC analysis showed an AUC of 0.90 (95% CI: 0.77 to 1.00) for grade 2 and 0.81 (85% CI: 0.63 to 0.98) for grade 1 or 2. Mean total dose-length product for the additional scans was 375±37 mGy.cm. Conclusions: In the elderly with severe AS, ECVCT performed with a 3 min post-contrast scan, can detect cardiac amyloid and could be used as a screening tool.